A new problem in inflammatory bladder diseases: Use of mobile phones! - (:unkn) unknown (BRAZILIAN SOC UROL, 2014)
Purpose: Technological developments provide a lot of conveniences to our lives. This issue is one of the risks that arise along with these conveniences. In our study we tried to understand the impact of electromagnetic waves from mobile phones on bladder tissue. Materials and Methods: Twenty-one adult male albino rats were divided into three equal groups. Group 1 was exposed to electromagnetic wave for 8 hours per day for 20 days and then their bladders were taken off immediately. Group 2 was firstly exposed to electromagnetic wave for 8 hours per day for 20 days then secondly another for 20 days without exposition to electromagnetic wave and then their bladders were taken off. Group 3 was the control group and they were not exposed to electromagnetic wave. Results: Under microscopic examination of bladder tissue, in the first group severe inflammatory cell infiltration was seen in lamina propria and muscle layer in contrast to intact urothelium. In the second group mild inflammatory cell infiltration was seen in lamina propria and muscle layer. The mean scores for the three groups were 5.5 +/- 2.5, 0.8 +/- 1.3 and 1.2 +/- 1.5 respectively. Mean score of group 1 was statistically higher than others (p = 0.001). Conclusion: Intensive use of mobile phones has negative impact on bladder tissue as well as the other organs. Keeping a minimum level of mobile phone use makes it easy to be kept under control of diseases in which inflammation is an etiologic factor.
Keywords: Urinary Bladder; Cellular Phone; Electromagnetic Radiation; INTERSTITIAL CYSTITIS; ELECTROMAGNETIC-RADIATION; NERVOUS-SYSTEM; MAST-CELLS; EXPOSURE; DAMAGE